PELAKSANAAN PROMOSI WISATA PADA MUSEUM BATAM RAJA ALI HAJI - Parhusip, Isabela; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to analyze and evaluate the implementation of tourism promotions at the Batam Raja Ali Haji museum using advertising, sales promotion, personal selling, direct marketing and public relations approaches. This research was conducted with the aim of finding out the effectiveness of promotional strategies carried out by tourism managers or museums in increasing visitor awareness and interest in the museum. The research method used is qualitative research. The theories of advertising, sales promotion, personal selling, direct marketing and public relations are used as a theoretical framework in analyzing the implementation of promotions. The research results show that promotional strategies involving advertising, sales promotion, personal selling, direct marketing and public relations have an important role in increasing visitor awareness and interest in the Batam Raja Ali Haji Museum tour. By implementing a promotional strategy through these 5 promotional mixes, it can provide maximum results in increasing tourist visits to the Batam Raja Ali Haji Museum. It is hoped that the results of this research can provide insight and guidance for Batam Raja Ali Haji Museum tourism managers in optimizing their promotional efforts. Keywords: Implementation, Promotion, Tourism, Museum, Batam